Real-World Efficacy and Safety of S-1 Monotherapy in Non-Small Cell Lung Cancer Management: Insights From a Multicenter Retrospective Cohort Study - I-Lin Tsai; Chien-Yu Lin; Po-Lan Su; Chien-Chung Lin; John Wen-Cheng Chang; Chen-Yang Huang; Yueh-Fu Fang; Ching-Fu Chang; Chih-Hsi Scott Kuo; Ping-Chih Hsu; Cheng-Ta Yang; Chiao-En Wu (Clinical Medicine Insights: Oncology)
Background: S-1, an oral chemotherapy combining tegafur, gimeracil, and oteracil, has shown efficacy comparable with docetaxel for advanced non-small cell lung cancer (NSCLC) in clinical trials. However, its real-world effectiveness and safety remain underexplored. Methods: This retrospective cohort study was conducted at 2 tertiary referral centers: National Cheng Kung University Hospital (NCKUH) from July 1, 2012 to July 1, 2023 (last follow-up in October 31, 2023) and Linkou Chang Gung Memorial Hospital (CGMH) from February 1, 2020 to January 31, 2023 (last follow-up in August 31, 2023). The study included 132 NSCLC patients receiving S-1 monotherapy (77 from CGMH and 55 from NCKUH). After excluding 31 patients with less than 2 weeks of treatment, 101 patients were analyzed. Results: The objective response rate (ORR) was 7.9%, and the disease control rate (DCR) was 44%. Median progression-free survival (PFS) and overall survival (OS) were 2.6 and 6.0 months, respectively. First-line or second-line S-1 therapy significantly improved DCR (61.1% vs 33.8%, P  = .008) and PFS (4.2 vs 2.3 months, P  < .001) compared with third-line or later use. Cox regression analysis confirmed earlier-line S-1 treatment (⩽ 2) as an independent predictor for PFS (hazard ratio: 2.01, 95% confidence interval: 1.15-3.51, P  = .014). Severe adverse events (grade ⩾ 3) occurred in 7.9% of cases. Conclusions: S-1 monotherapy demonstrated comparable effectiveness and manageable toxicity in real-world settings, with significantly better outcomes when used as first-line or second-line treatment in NSCLC.